PULLER®: ferramenta educativa para auxílio ao aprendizado sobre proteção radiológica - JAQUELINE SANT' ANNA LAUREANO PEREIRA; DANIEL LAUREANO PEREIRA; SAMUEL QUEIROZ PELEGRINELI; JOSONILTON COSTA MORAES RÊGO; LUCIANO SANTA RITA OLIVEIRA (Brazilian Journal of Radiation Sciences)
RESUMO